V objemu besed: razvijanje družinske pismenosti (University of Maribor Press, 2017)
Developing Family Literacy Hugged by Words: a guide for parents. Monograph Hugged by Words is a result of a research project by the same name, financed by the Ministry of Culture of RS (duration from October 2016 till November 2017). Its area is encouragement of family reading or family literacy, a part of reading literacy (essential for successful inclusion of people in the society) and includes intergenerrational reading in all areas of kindergarten work (language, art, society, nature, mathematics, movement) and in all areas of child’s development (cognitive, social, emotional, aesthetical, moral-ethical and motivational). There are guidelines for the family literacy model, followed by thematic chapters (Areas of Child’s Development, Literature and Language, Art, Society, Nature, Mathematics, Movement, Library, Reading Badge), contributing to raising awareness of the importance of reading as a lifelong process by connecting a particular area of kindergarten work with early literacy. We define family literacy as various family activities, linked to literacy in the widest sense, when all family generations cooperate, the result being joint learning. With the factors encouraging reading literacy (IFLA, 2006: being surrounded with reading material, reading to the child, the adult as a reading model) various encouragements are presented for building a positive relationship towards reading culture and habits, linked to literacy.